Reactivation of IgG-switched memory B cells by BCR-intrinsic signal amplification promotes IgG antibody production - Lutz, Johannes (Nat Commun, 2015)
Secondary antibody responses are marked by faster kinetics, improved antibody affinity and a switch from IgM to other immunoglobulin isotypes, most notably IgG, compared with primary responses. These changes protect from reinfection and represent the principle of most vaccination strategies. Yet, the molecular mechanisms that underlie B-cell memory responses are unclear. Here we show, by inactivating the immunoglobulin tail tyrosine (ITT) signalling motif of membrane-bound IgG1 in the mouse, that the ITT facilitates maintenance and reactivation of IgG-switched memory B cells in vivo. The ITT motif equips IgG-switched cells with enhanced BCR signalling capacity, which supports their competitiveness in secondary immune reactions and drives the formation of IgG-secreting plasma cells even in the absence of T-cell help. Our results demonstrate that ITT signalling promotes the vigorous production of IgG antibodies and thus provide a molecular basis for humoral immunological memory.